Implied cost of capital and mutual fund performance - Mario Hendriock (University of Cologne, Centre for Financial Research (CFR), 2020)
This study provides evidence for a positive association between mutual fund holdings'implied cost of capital (ICC) and future performance. Consistent with large transactioncosts of ICC-based investments impeding their exploitation and employing a ICC-basedstrategy reflecting skill, family-level trading efficiency and manager-level SAT scorepositively correlate with fund-level ICC. A negative association between ICC and mid-year risk shifting corroborates the notion of fund managers decisively choosing andrelying on high-ICC strategies. Institutional investors able to identify funds with highICC direct their investments accordingly, whereas flows of retail funds are unaffected,consistent with limited investor attention and financial literacy.
Keywords: G11; G14; G17; G23; G31; M41; 330; implied cost of capital; mutual funds; portfolio choice; financial forecasting